Integrating Land Use Planning with Regenerative Agriculture: A Synergistic Approach to Enhance Sustainable Agricultural Productivity and Ecosystem Resilience - Ahmad Arif Darmawan; Suntoro Suntoro; Eni Kusumawati (Journal of Applied Agricultural Science and Technology, 2026)
Land-use planning and regenerative agriculture are increasingly recognised as complementary strategies for addressing declining soil quality, land degradation, and the need for more resilient food systems. The present study investigates the manner in which the integration of regenerative practices within land-use planning frameworks contributes to sustainable agricultural productivity and ecosystem stability. A bibliometric analysis of 70 publications from 2015–2025 using VOSviewer has identified key thematic clusters, including climate–resilience, sustainable productivity, spatial governance, green infrastructure, and environmental monitoring. The findings show that regenerative practices, such as no-till systems, cover cropping, diversified rotations, and agroforestry, support soil restoration, carbon accumulation, and water retention. Land-use planning provides the spatial, institutional, and regulatory mechanisms needed to align these practices with land suitability, environmental carrying capacity, and regional planning objectives. Evidence from marginal lands (S2 and S3) highlights the effectiveness of regenerative methods in enhancing productivity when integrated with suitability assessments and long-term planning. A case study of Brazil’s Carbon Farming Initiative demonstrates how coordinated land-use policies, spatial data, and public–private partnerships can scale regenerative systems and reduce greenhouse gas emissions. The analysis further shows that this integration supports multiple Sustainable Development Goals, particularly those related to food security, clean water, climate action, and terrestrial ecosystem conservation. Key barriers, including policy fragmentation, limited farmer adoption, and technological constraints, are addressed through recommendations involving financial incentives, farmer training, geospatial monitoring, and precision agriculture tools. The study provides a comprehensive understanding of how land-use planning can operationalise regenerative agricultural strategies to enhance landscape resilience, improve resource efficiency, and strengthen long-term sustainability across agricultural regions.